DESAIN DAN ANALISIS KNALPOT BERBASIS SPONGESTEEL TERHADAP GAS BUANG CO, HC, DAYA, DAN SFC PADA MESIN SEPEDA MOTOR - Yuniarto Agus Winoko; Hari Rarindo; Bambang Hertomo (Universitas Nusa Cendana, 2019)
The increase in the number of motorized vehicles increases every year so that air pollution also increases. Lack of public awareness about reforestation makes the air difficult to circulate. The number of motorized vehicles is also a major factor in increasing air pollution. Exhaust emissions from motorized vehicles are harmful pollutants to the human body. Exhaust gas from motor vehicles contains toxic compounds, one of which is carbon monoxide (CO) and hydro carbon (HC) which are very dangerous for the environment and humans. The purpose of the study is to make a tool that can control exhaust emissions. Sponge steel-based muffler uses sponge steel as a means of continued combustion of the exhaust gas, sponge steel heating is produced from the heat of the exhaust gas itself. The heat from the sponge steel coupled with the pressure from the exhaust gas itself will increase the heat from the sponge steel, so the sponge steel can burn. With the heat from the sponge steel the gas that has not been burned in the combustion chamber will be burned again in the exhaust by a sponge steel, so that CO and HC gas will be burned with O2, CO2, O2 and H2O gases will be obtained. The method of the study is experimental methods. An experimental research study conducted by manipulation that aims to determine the results of manipulation of individual behavior observed. The data observed in this study included a exhaust gas emissions, power, and specific fuel consumtion (SFC). The result of the study, Sponge steel based exhaust can reduce exhaust emissions, in HC compounds can decrease by 24.79% and CO decreases to 29.70%, reduced power by 5.64% is not too significant from standard exhaust, and SFC decreased by 3,12%.